Radical Incrementalism. (April 2015) - Halpern, David; Mason, Danielle
A strategy of 'radical incrementalism' is herein advocated as a useful approach to policy making which makes proper use of evaluation. It is argued that small, incremental changes, supported by small-scale and tightly focused evaluations, are under-utilised as an approach to cost effective policy improvement.